Le contrôle juridictionnel de l'action administrative devant les juridictions anglaises - Slynn, Sir Gordon (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
This article outlines the difficulties which were felt to exist in the prerogative orders of certiorari, mandamus and prohibition in the United Kingdom, despite important developments which had taken place in their use. It describes in detail the recommendations of the Law Commission and the changes introduced both by Rules of Court and legislation. The former procedures are replaced by an application for judicial review, though the basis upon which relief is granted remains substantially the same. Recent cases show the way in which the new procedure has developed. Distinctions are drawn between the test to be applied on the application for leave and on the final hearing, and between the proceeding by way of judicial review to challenge the acts of public authorities and actions where purely private rights are claimed. This article shows the way in which the possibility of exceptions to this latter distinction has been established and suggests that the ambit of the new procedure is still in course of development.